Initial Description of Breast Care for Fluency of Breast Milk Production in Primiparous Postpartum Mothers (Early Study of Electronic Bra Development) - Ni Luh Desi Mahariani; Diyah Fatmasari; Edy Susanto (JURNAL KEBIDANAN, 2023)
Breast Milk (ASI) is the best nutrition for babies. Exclusive breastfeeding is given to babies within 6 months. Exclusive breastfeeding is influenced by fluency of breast milk production. Efforts to increase breast milk by doing breast care. The purpose of the study was to find out description of breast care for fluency of breast milk production in primiparous postpartum mothers and the feasibility of using electronic bra development (early study of the electronic bra development). The research method used a descriptive observational and qualitatively analyzed which was carried out in November - December 2022. The sampling technique used simple random sampling with sample of primiparous postpartum mothers, total of 36 respondents. The data collection technique was by distributing questionnaires in the form of written interview guidelines. The results of this study are postpartum mothers immediately breastfeed if their breasts feel tense 70%, feel happy when breastfeeding their baby 50%, breastfeed 8 times 70%, produce little milk but continue to breastfeed 80%, breast milk is not fluency 70%, breastfeed in time 15 minutes 80%, baby feels dissatisfied with breastfeeding 80%, immediately breastfeeds if one breast is full with 100% milk, sufficient milk by giving breast milk 60%, baby's sucking reflex is quite good 40%. The results of the expert test show that the category is very feasible. The conclusion of this study is that primiparous postpartum mothers do not perform optimal breast care and development of electronic bra is suitable for use to increase the fluency of breast milk production.